Norwegian male U14 soccer players have superior running capacity compared to Icelandic players - Benediktsson, S.; Johannsson, E.; Rygh, C. B.; Gundersen, H. (Frontiers in Sports and Active Living, 2024)
The organisation and development strategies of youth soccer differ between Norway and Iceland. Whether this affect physical capacity is unknown. Thus, the first aim of the present study is to compare physical capacity between players from Iceland and Norway. Secondary aim is to assess associations between biological maturity and physical capacity in the Icelandic players since an association previously has been shown among the Norwegians. There were 48 U14 players from Iceland included and 103 players from Norway. Bone age (BA), measured with left-wrist x-ray, was used as an indicator of biological maturity. To measure physical capacity, 40 metre (m) linear sprint, standing long jump (SLJ), countermovement jump (CMJ), the Yo-Yo intermittent recovery test (IR1-test) and a maximal oxygen uptake test (VO2max) were used. Training load was assessed by questionnaire. The results showed that the Norwegian players ran faster (5.90 ± 0.38 vs. 6.37 ± 0.44 s, p < .001), had better intermittent endurance capacity (1,235 ± 461 vs. 960 ± 423 m, p < .001) and higher VO2max, (60.3 ± 6.5 vs. 54.8 ± 5.3 ml·kg-1·min-1, p < .001) than the Icelandic players. The players from Norway reported a higher number of weekly organised soccer training hours than the Icelandic. We also found significant correlations between BA and performance on 40 m linear sprint (r = -.566, p < .001), SLJ (r = .380, p = .008) and CMJ (r = .354, p = .014) among the Icelandic players. Moreover, no correlations were found between BA and VO2max or intermittent endurance capacity. In conclusion, the Norwegian players ran faster and had better VO2max and intermittent endurance capacity than the Icelandic players. Biological maturity level was associated with speed and jumping performance in U14 soccer players in Iceland, but not with VO2max or intermittent endurance capacity. Findings indicate that more research is needed to investigate the influence of different organisation and structure of youth soccer between the two countries on physical capacity.